Developing a PBL Based E-Module on Plant Structure and Development Subject with Formative Assessment to Improve Students’ Collaborative Problem-Solving (CPS) Skill - Rahmah, Ana Novia; Sari, Murni Sapta; Balqis, Balqis (BIOEDUKASI, 2024)
Collaborative problem solving (CPS) is a learning activity in which students work in small groups to achieve common goals. Students’ CPS skills can be assessed through observation, self-assessment, and peer assessment. To enhance CPS skills, the Problem Based Learning (PBL) model can be applied. This study aims to develop a PBL-based e-module on Plant Structure and Development specifically on pollination and fertilization with self-assessment and peer assessment to improve the students’ collaborative problem-solving skills. The research and development method in this study follows the pattern established by Lee and Owens. The population of this study consisted of Biology Education students at UM (Universitas Negeri Malang) and students from private universities in Malang. Purposive sampling was used for sample selection. The instruments used were survey and questionnaire. Based on the results of pre-test and post-test, it can be concluded that the use of the e-module can improve the students' CPS skills. Based on the validity, practicality, effectiveness tests; as well as implementation of the learning syntax, it is known that the e-module is valid and practical without any revisions, moderately effective, and very good in terms of the implementation of the learning syntax.